A teaching note on the controllability "Principle" and performance measurement. Issue 3 (4th September 2017) - Schwartz, Steven T.; Spires, Eric E.; Young, Richard A.
Abstract : Purpose: The purpose of this note is to expose accounting students and others to recent findings in management control, specifically to the relationship between the informativeness of a performance measure and its usefulness in performance evaluation. Design/methodology/approach: Numerical examples illuminate key ideas and are easy to follow and replicate by students. Findings: Seemingly in contradiction to the controllability principle, performance measures that are informative about actions taken by employees are not necessarily useful for performance evaluation. This occurs when the performance being measured is related to an intermediate task, such as prepping items prior to final assembly. If prepping is an important factor in the quality of not only the intermediate good but also the finished good, and the quality of the finished good can be reasonably measured, it may not be useful to measure the prepping performance. This result holds even if obtaining the intermediate measure is costless and the intermediate measure provides unique information on the effort given to the intermediate task. Originality/value: Opportunities to measure employees' intermediate outputs are ubiquitous; therefore, judicious decisions should be made regarding the use of limited monitoring resources. This note contains intuitive, easy-to-follow illustrations (based on recent findings) that will help students and others identify situations where such evaluations are more and less useful.